Analysis and Design of Data Warehouse at Bank M - Anwar, Agus; Pradipta, Danan; Aryani, Sri (International Journal of Engineering and Emerging Technology, 2018)
Banking has a very strategic role in supporting the running of the economy and national development considering its function as an intermediary institution, payment transaction organizer, and monetary policy transmission tool. The banking industry, data warehouse is something that is very important existence, because with this data warehouse, performance analysis of a bank will be much easier to do. The HOLAP method of data warehouse banking processing can present the desired information quickly. With the support of data warehouses, corporate leaders can be more helpful in making decisions faster and more precise.